ESTABLISHMENT OF MONOGRAPH OF ACORUS CALAMUS LINN. RHIZOMES - Kaushik, Rahul; Sharma, Binu (Journal of Drug Delivery and Therapeutics, 2012)
Acorus calamus Linn. (Araceae) is a semi-aquatic, perennial, aromatic herb with creeping rhizomes, arching tapered reed-like leaves and minute yellow-green flowers growing wild in wet areas like edges of streams and around ponds & lakes, in ditches and seeps and also cultivated. It is widely distributed throughout India and Ceylon, ascending the Himalayas up to 6600 feet in Sikkim, plentiful in the marshy tracts of Kashmir, Sirmoor, Manipur and Naga Hills. The rhizomes are considered to possess antiâ€spasmodic, carminative and anthelmintic, aromatic, expectorant, nervine, sedative, stimulant and nauseating properties. Medicinally used for the treatment of epilepsy, mental ailments, chronic diarrhea, dysentery, bronchial catarrh, intermittent fevers and glandular and abdominal tumors. The current study was therefore carried out to identify requisite pharmacognostical details i.e. organoleptic, microscopical, fluorescence analysis, quantitative microscopy and physical constants such as ash value and extractive values of the fruit. The extacts were subjected to preliminary phytochemical screening. The study revealed specific indices for the particular crude drug which will be useful in identification, control on adulterations of the crude drug and preparation of a monograph of the drug.